Socio-economic transformation in South Africa: Black Economic Empowerment and small, medium and micro enterprises - Diana Sanchez (Danish Institute for International Studies (DIIS), 2006)
Economic and social transformation of post apartheid South Africa has been a central goal for the democratic regime but broad empowerment of the majority of black South Africans is yet to take place. Small, Medium and Micro Enterprises (SMMEs) have been recognized as central for economic growth and transformation since the mid-1990s, and have developed under an economic framework influenced by the state's transformation strategies, particularly Broad-Based Black Economic Empowerment (BBBEE). Yet, little research is available on the opportunities and challenges faced by SMMEs in the context of the BEE strategy, and on their potential contribution for socio-economic transformation. This paper aims to enrich this debate by looking at the synergies between SMMEs and the BEE strategy, and by examining the potential that SMMEs hold to facilitate BEE. While acknowledging the limitations of the data available, the overall conclusion is that positive interactions between the SMME and BEE frameworks can contribute to the empowerment of more disadvantaged South Africans and therefore to meaningful socio-economic transformation. SMMEs will play a prominent role in the second decade of our democracy and beyond as we seek to accelerate economic growth, reduce unemployment and bridge the gap between the first and second economies. Trade and Industry minister Mpahlwa, cited in Sowetan, 20 September 2005
Keywords: 330; Ethnische Diskriminierung; Rassenpolitik; Wirtschaftspolitik; Mittelstandspolitik; KMU; Entwicklung; Südafrika